Adaptation to climate change for smallholder agriculture in Kenya: Community-based perspectives from five districts - Roncoli, Carla; Okoba, Barrack; Gathaara, Violet; Ngugi, Jane; Nganga, Teresiah (International Food Policy Research Institute, 2010)
This project note presents the results of a community-based, participatory assessment of local perspectives on climate change and adaptation in five sites in Kenya. The sites reflect a wide range of climatic, agroecological, and socioeconomic conditions, including humid/semi-humid areas in western Kenya, the humid zone of the central highlands, semi-arid areas in the Rift Valley, eastern Kenya, and arid areas of northeastern Kenya.